2008
DOI: 10.2459/jcm.0b013e32801462d4
|View full text |Cite
|
Sign up to set email alerts
|

Role of anticoagulation therapy after pulmonary vein antrum isolation for atrial fibrillation treatment

Abstract: Stopping OAT 3 months after ICE-PVAI seems to be safe in patients without AF recurrences after the first 3 months following ablation. Further randomized-controlled studies are needed to confirm these preliminary data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…As far as we know, this is the largest set of case records compiled on patients who have undergone long-term suspension of OAT, in terms of both the total number of patients (n ϭ 2,692) and the number of moderate-/high-risk patients (723 patients with CHADS 2 score 1 and 347 patients with CHADS 2 score Ն2), in whom OAT is recommended or suggested by the international guidelines (1,2). Our results are substantially in line with those of other recently published retrospective studies involving smaller populations and shorter follow-up periods (13)(14)(15)(16). In particular, they are similar to those observed by Nademanee et al (14).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…As far as we know, this is the largest set of case records compiled on patients who have undergone long-term suspension of OAT, in terms of both the total number of patients (n ϭ 2,692) and the number of moderate-/high-risk patients (723 patients with CHADS 2 score 1 and 347 patients with CHADS 2 score Ն2), in whom OAT is recommended or suggested by the international guidelines (1,2). Our results are substantially in line with those of other recently published retrospective studies involving smaller populations and shorter follow-up periods (13)(14)(15)(16). In particular, they are similar to those observed by Nademanee et al (14).…”
Section: Discussionsupporting
confidence: 95%
“…Patients with a thromboembolic risk of 2% per year or less do not benefit substantially from OAT, and according to the international guidelines should not be treated with this therapy (1). All of the studies, included ours, conducted to date on patients who have undergone successful AF ablation report a decidedly lower incidence of TE than that required by the guidelines (13)(14)(15)(16). Another reason for administering OAT after AF ablation is that extensive LA lesions might impair LA function, as observed by Lemola et al (24) on performing LA circumferential ablation in patients with paroxysmal AF.…”
Section: Discussionmentioning
confidence: 83%
“…Warfarin should be continued in patients with a CHADS 2 (congestive heart failure, hypertension, age, diabetes, prior stroke or transient ischemic attack) score ≥ 2. The safety of discontinuing anticoagulation 3 months after pulmonary vein isolation was evaluated in 85 consecutive patients [28]. Anticoagulation was not stopped in patients with AF recurrence, severe pulmonary vein stenosis, poor atrial contractility on TEE, or another indication for anticoagulation.…”
Section: Postprocedural Managementmentioning
confidence: 99%
“…In addition, several studies supported feasibility and safety of discontinuing OAC after successful ablation reporting low thromboembolic and reduced bleeding risks [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Rossillo et al [11] suggested atrial contractility assessment at transesophageal echocardiography amongst the criteria for continuing/discontinuing OAC following 9 successful AF ablation. A transesophageal echocardiographic evaluation was performed in all patients at 3-month follow-up examination.…”
mentioning
confidence: 99%